1998
DOI: 10.4269/ajtmh.1998.59.933
|View full text |Cite
|
Sign up to set email alerts
|

Human leptospirosis in the Seychelles (Indian Ocean): a population-based study.

Abstract: Abstract. A leptospirosis surveillance program was carried out for 12 months on the entire population of the Seychelles. Diagnosis was assessed by both microagglutination test and polymerase chain reaction (PCR) assay. In this population of 74,331, leptospirosis was clinically suspected in 125 subjects and confirmed in 75 patients (incidence of 101 per 100,000; 95% confidence interval ϭ 79-126). Leptospirosis was more frequent in middle-aged males with environmental exposure. Eight serogroups were identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
78
4
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 26 publications
15
78
4
5
Order By: Relevance
“…The study was a population-based surveillance conducted between 1 April 1995 and 31 March 1996. The detailed study design was reported previously (YERSIN et al, 1998). In brief, all doctors of the country were asked to refer during this period any patient who had fever or any of the following signs or symptoms: myalgia, tender liver, jaundice, ARF, bleeding tendency, radiological lung infiltrates, and meningism which could not be accounted for by a definite diagnosis other than leptospirosis.…”
Section: Study Area and Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was a population-based surveillance conducted between 1 April 1995 and 31 March 1996. The detailed study design was reported previously (YERSIN et al, 1998). In brief, all doctors of the country were asked to refer during this period any patient who had fever or any of the following signs or symptoms: myalgia, tender liver, jaundice, ARF, bleeding tendency, radiological lung infiltrates, and meningism which could not be accounted for by a definite diagnosis other than leptospirosis.…”
Section: Study Area and Populationmentioning
confidence: 99%
“…19951. ' Leptospirosis is endemic in Seychelles: Previous reports indicated a high annual incidence ranging from 45 to 101 per 100 000, and frequent hepatic, renal, and haemorrhagic complications (PINN, 1992;YERSIN et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary hemorrhage occurred in 14 of 75 patients (19%) in the Seychelles, causing the deaths of six patients [27]. In a 1987 epidemic in Korea, 37 of 93 patients (40%) with leptospirosis had hemoptysis, massive in all 5 patients who died [28].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…This was related to the fact that none of 62 control sera (from laboratory staff) gave similar titres and no cross-reactions to other leptospiral serovars could be demonstrated [1]. A leptospirosis surveillance programme in the Seychelles identi®ed L. fainei by a PCR assay and by an MAT as the second most frequent serotype infecting human patients with suspected leptospiral infection, and a correlation to severe cases of human infection was con®rmed [2].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the serogroups Icterohaemorrhagiae, Sejroe and Saxkoebing have most clinical relevance. Recently, L. fainei has been suspected as a new human pathogen [1,2]. L. fainei serovar Hurstbridge was ®rst isolated from culled sows in Australia in 1994 [3], and it is both a new species and a previously unknown serogroup (Hurstbridge).…”
Section: Introductionmentioning
confidence: 99%